Development of A Coaching-Based Teaching Module to Improve the Achievement of Santri at Pondok Tahfidz Alkhair Padang - Sherli Dwi Andri Saputri; Hafidz Ardi; Prima Aswirna (CV. Edujavare Publishing, 2026)
Islamic education plays a strategic role in shaping a generation that excels intellectually, spiritually, and religiously, as reflected in the routine coaching program at Pondok Tahfidz Alkhair Padang, which focuses on tilawah (Qur'anic recitation), tahfidz (memorization), tartil, the Qur'an Recitation Contest (MSQ), juz 30, and the call to prayer (azan). However, the implementation of this coaching has so far relied solely on the verbal direction of the instructors without being supported by a specifically designed teaching module, so that the material delivered remains unstructured and the santri (students) lack a resource for independent learning. This study aims to develop a valid and practical coaching-based teaching module, as well as to design a plan for testing its effectiveness in improving the achievement of santri at Pondok Tahfidz Alkhair Padang. The study is designed using the Research and Development (R&D) method with the ADDIE model, which covers the stages of analysis, design, development, implementation, and evaluation. The research subjects are planned to involve tahfidz content experts, learning experts/pesantren practitioners, and the santri of Pondok Tahfidz Alkhair Padang as trial subjects. Data will be collected through expert validation sheets and a Likert-scale santri response questionnaire, then analyzed descriptively and quantitatively in percentage form. This article presents the conceptual framework, theoretical review, and methodological design of the research, as the stages of product development, validation, and field trials have not yet been carried out. The resulting teaching module is expected to serve as a systematic coaching guide for instructors as well as an independent learning resource for the santri of Pondok Tahfidz Alkhair Padang.